1994
DOI: 10.1080/01140671.1994.9513835
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and regional variation in budbreak and flowering of kiwifruit vines in New Zealand

Abstract: Measurements of the timing and amount of budbreak and flowering in 'Hayward' kiwifruit were made over 4 years in six regions of New Zealand. There was a large variation in the vine attributes measured. The number of flowers produced/winter bud varied 5-fold between the worst site-year combination and the best. The time of 50% budbreak varied by 32 days and the time of 50% flowering by 25 days. The proportion of flowers on the distal (tip) two buds ranged in a single year from a low of 10% at one site to > 65% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 24 publications
(31 reference statements)
4
24
0
Order By: Relevance
“…These results are consistent with the controlled environment experiments in container grown vines (Warrington & Stanley 1986;McPherson et al 1988). The regression model derived from field data to predict the development rate from end of dormancy to budburst (Equation 5) gave delays in budbreak of 17 days for a reduction in temperature from 12 to 8°C and 16 days for a reduction in temperature from 19 to 10°C.…”
Section: Dormancy To Budburstsupporting
confidence: 90%
See 2 more Smart Citations
“…These results are consistent with the controlled environment experiments in container grown vines (Warrington & Stanley 1986;McPherson et al 1988). The regression model derived from field data to predict the development rate from end of dormancy to budburst (Equation 5) gave delays in budbreak of 17 days for a reduction in temperature from 12 to 8°C and 16 days for a reduction in temperature from 19 to 10°C.…”
Section: Dormancy To Budburstsupporting
confidence: 90%
“…Our model gives phase durations of 47 and 81 days at the same temperatures. McPherson et al ( 1988) found a phase duration difference of 97 days between mean temperatures of 19 and 10°C, with our model giving 96 days. The controlled environment experiments show an increase of 8-10 days/°C reduction of temperature.…”
Section: Budburst To Floweringsupporting
confidence: 50%
See 1 more Smart Citation
“…Although applying hydrogen cyanamide to kiwifruit vines increases budbreak and flowering, it does not fully compensate for insufficient winter chilling, so flower production still decreases as mean winter temperatures increase (McPherson et al 2001). Consequently, we would expect to see a reduction in both budbreak and flowering if the LD treatments delayed the onset of the accumulation of winter chilling (McPherson et al 1994). Although the LD treatments resulted in a substantial reduction in flowering, the amount of budbreak was not affected and so the LD treatments do not appear to effect the accumulation of winter chilling in kiwifruit.…”
Section: Did the Ld Treatments Affect The Accumulation Of Winter Chilmentioning
confidence: 99%
“…Chev.) C. F. Liang et A. R. Ferguson 'Hayward' kiwifruit, the timing and amount of flowering have been used to assess the effects of temperature (McPherson et al 1994), growth regulators (Henzell et al 1991), shading (Snelgar et al 1992), thinning (Burge et al 1987), defoliation (Buwalda & Smith 1990), and cane tipping (Manson et al 1991) on vines. However, there have been no studies of how flowering varies within a kiwifruit vine.…”
Section: Introductionmentioning
confidence: 99%